Use Of Apitherapy: A Sweet Approach To Bony Healing Of Extracted Tooth Socket - Tahera Ayub; Mehwash Kashif; Sahar Abbasi; Mirza Hamid Baig; Syeda Arzoo Azeem; Abdul Aleem (Journal of Rawalpindi Medical College)
Objective: To determine the effect of honey in enhancing the height of bony socket healing after tooth extraction.